Reinforced polypropylene composition
By developing a polyolefin composition containing a heterogeneous polymer and polyethylene composition and using melt blending and shear processing technology, the negative impact of the deterioration of characteristics of polyolefin materials and the use of inorganic fillers on environmental sustainability and logistics costs during mechanical recycling is solved, and the high mechanical properties, low density and good recyclability of the material are achieved.
Patent Information
- Application Number
- CN202280067363.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-10-28
- Filing Date
- 2022-10-10
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-10-10
AI Technical Summary
The characteristics of existing polyolefin materials deteriorate during mechanical recycling, and the use of inorganic fillers has a negative impact on environmental sustainability and logistics costs.
A polyolefin composition is developed, comprising 15-80% heterophase polymer and 20-85% polyethylene composition, through melt blending and shear processing techniques, to form materials with improved mechanical properties and reduced density.
The material does not deteriorate significantly after multiple processing, has high tensile modulus and impact resistance, and is also low in density, which reduces logistics costs and improves environmental sustainability.
Smart Images

Figure BDA0004775287660000091 
Figure BDA0004775287660000092 
Figure BDA0004775287660000131
Abstract
Description
Technical Field
[0001] The present disclosure relates to a polyolefin composition and an injection molded or 3D printed article obtained therefrom. Background Art
[0002] To compete with other engineering materials, polyolefins are often reinforced with inorganic fillers such as glass fibers or minerals.
[0003] Filled polyolefins have several advantageous properties, such as high strength and stiffness, and are widely used in many industrial fields, such as in the automotive field for injection molding of interior and exterior parts.
[0004] Even though the presence of inorganic fillers improves the mechanical properties of polyolefins, it also has a negative impact on the environmental sustainability of the filled materials.
[0005] The mechanical properties of mechanically recycled glass-filled polyolefins deteriorate over time because the fibers are damaged and shredded at each recycling step. As a result, inorganically filled plastic materials have a shorter life cycle than unfilled materials and they quickly turn into disposable waste.
[0006] When chemically recycled, the inorganic fillers must be separated from the polyolefin matrix, increasing process complexity and reducing sustainability.
[0007] In addition, plastics filled with conventional inorganic fillers have a high density. The heavier the plastic material, the higher the mass of the vehicle in which the material is transported. This results in higher fuel consumption for combustion engine vehicles or reduced driving range for electric vehicles, thus increasing the environmental impact of the logistics of the filled material.
[0008] Self-reinforced polyolefin solutions have been developed to provide reinforced polyolefins without inorganic reinforcing agents.
[0009] Timo Hees et al., in Polymer, Vol. 151, August 29, 2018, pp. 47-55, disclose an all-PE self-reinforced composite obtained by compounding conventional HDPE with a bimodal reactor blend of UHMWPE (ultra-high molecular weight polyethylene) and HDPE wax. The resulting trimodal self-reinforced polyethylene has improved mechanical properties.
[0010] However, past attempts to reinforce polypropylene with UHMWPE have either achieved poor results due to the poor miscibility of UHMWPE with polypropylene, or may have used unconventional and energy intensive processes.
[0011] X. Wang et al., Journal of Polymer Science, Vol. 100, 3495-3509 (2006), achieved satisfactory results for reinforcing propylene homopolymers with UHMWPE in the presence of EPDM when the polyolefins were melt blended in a co-rotating four-screw extruder. The results obtained using conventional twin-screw extruders were inferior.
[0012] T. Hees et al., ACS Applied Polymer Materials, 2021, 3, 3455-3464, obtained poor results in reinforcing iPP with reactor blends of low amounts of UHMWPE and PE wax.
[0013] Patent application US 2014 / 0066574 A1 teaches obtaining a reinforced injection molded article by pultruding 60 to 85 wt. % of a highly flowable thermoplastic resin into 15 to 40 wt. % of UHMWPE fibers.
[0014] In this context, there remains a need for reinforced polyolefins having improved mechanical properties relative to the same unreinforced polyolefin, in particular simultaneously increased tensile strength and impact resistance, low density and improved recyclability relative to inorganically filled polyolefins. Summary of the invention
[0015] The present disclosure provides a polyolefin composition (I), comprising:
[0016] (A) 15 to 80 weight percent of a heterophasic polymer composition comprising:
[0017] (a) 50 to 80 wt.% of at least one propylene polymer selected from the group consisting of propylene homopolymers, propylene and ethylene and / or at least one copolymer of the formula CH2=CHR 1 Copolymers of α-olefins and mixtures thereof, wherein R 1 is a linear or branched C2 to C8 alkyl group, the copolymer comprising up to and including 10.0 wt%, preferably from 0.05 to 8.0 wt%, based on the weight of (a), of units derived from ethylene and / or α-olefins;
[0018] (b) 20 to 50% by weight of ethylene and at least one compound of the formula CH2=CHR 1 At least one copolymer of an α-olefin, wherein R 1 is a linear or branched C2 to C8 alkyl group, the copolymer comprises from 10 to 40% by weight, preferably from 20 to 35% by weight, based on the weight of (b), of units derived from α-olefins,
[0019] wherein the amounts of components (a) and (b) are based on the total weight of (a) + (b);
[0020] (B) 20 to 85 weight percent of a polyethylene composition comprising:
[0021] (i) 25 to 85 wt.% of a polyethylene component having a weight average molecular weight Mw(i) equal to or higher than 1,000,000 g / mol as measured by gel permeation chromatography;
[0022] (ii) 10 to 65% by weight of a polyethylene component having a weight average molecular weight Mw(ii) equal to or lower than 5,000 g / mol as measured by gel permeation chromatography,
[0023] wherein the polyethylene composition (B) comprises at least 70 wt% of (i)+(ii), and the amounts of (i) and (ii) are based on the total weight of the polyethylene composition (B), the total weight being 100%,
[0024] And wherein the amounts of components (A) and (B) are based on the total weight of (A) + (B).
[0025] The present disclosure also provides a process for manufacturing a shaped article, the process comprising subjecting the flow rate of the molten polyolefin composition (I) to a temperature equal to or greater than 50 s. -1 The shear rate.
[0026] In another aspect, the present disclosure provides a use of a polyethylene composition (B) comprising:
[0027] (i) 25 to 85 wt.% of a polyethylene component having a weight average molecular weight Mw(i) equal to or higher than 1,000,000 g / mol as measured by gel permeation chromatography;
[0028] (ii) 10 to 65% by weight of a polyethylene component having a weight average molecular weight Mw(ii) equal to or lower than 5,000 g / mol as measured by gel permeation chromatography,
[0029] wherein the polyethylene composition (B) comprises at least 70 wt% of (i)+(ii), and the amounts of (i) and (ii) are based on the total weight of the polyethylene composition (B), the total weight being 100%,
[0030] As a reinforcing masterbatch of a heterophasic polymer composition (A), the reinforcing masterbatch comprises:
[0031] (a) 50 to 80 wt.% of at least one propylene polymer selected from the group consisting of propylene homopolymers, propylene and ethylene and / or at least one copolymer of the formula CH2=CHR 1 Copolymers of α-olefins and mixtures thereof, wherein R 1 is a linear or branched C2 to C8 alkyl group, the copolymer comprising up to and including 10 wt%, preferably from 0.05 to 8 wt%, based on the weight of (a), of units derived from ethylene and / or α-olefins;
[0032] (b) 20 to 50% by weight of ethylene and at least one compound of the formula CH2=CHR 1 At least one copolymer of an α-olefin, wherein R 1 is a linear or branched C2 to C8 alkyl group, the copolymer comprises from 10 to 40% by weight, preferably from 20 to 35% by weight, based on the weight of (b), of units derived from α-olefins,
[0033] The amounts of components (a) and (b) are based on the total weight of (a) + (b).
[0034] The polyolefin composition (I) has improved mechanical properties, in particular a high tensile modulus and a high tensile strength in combination with a high impact resistance.
[0035] The polyolefin composition (I) also has a significantly reduced density compared to heterophasic polyolefin compositions (A) reinforced with conventional inorganic fillers, such as glass fibers.
[0036] The polyolefin composition (I) can be easily converted into shaped articles using conventional extruders (such as twin-screw extruders) with little or no modification of conventional process and equipment settings.
[0037] Furthermore, the mechanical properties of the polyolefin composition (I) do not significantly deteriorate after multiple processing, allowing multiple recycling of the polyolefin composition (I), which results in improved environmental sustainability of the polyolefin composition (I) relative to polyolefin compositions containing conventional inorganic fillers.
[0038] Although a number of embodiments are disclosed, other embodiments will become apparent to those skilled in the art from the following detailed description. As will be apparent, certain embodiments as disclosed herein are capable of modification in various obvious respects without departing from the spirit and scope of the claims presented herein. Therefore, the following detailed description is to be construed as illustrative in nature and not restrictive. DETAILED DESCRIPTION
[0039] In the context of this disclosure;
[0040] - Unless otherwise stated, percentages are expressed by weight. Unless otherwise stated, the total weight of the composition adds up to 100%;
[0041] - the term "blend" when referring to polymers refers to reactor-made blends (i.e. blends of at least two polymer components obtained directly from a polymerization process), mechanical blends (i.e. blends obtained by melt mixing at least two different polymer components) and combinations of both;
[0042] - when the term "comprising" refers to a polymer or polymer composition, mixture or blend, the term should be interpreted as meaning "comprising or consisting essentially of";
[0043] - The term "consisting essentially of" means that in addition to the mandatory ones, other components may also be present in the polymer or polymer composition, mixture or blend, provided that the essential characteristics of the polymer or composition are not materially affected by their presence. Examples of components that do not materially affect the characteristics of the polymer or polyolefin composition, mixture or blend when present in conventional amounts are catalyst residues, antistatic agents, melt stabilizers, light stabilizers, antioxidants and antacids.
[0044] In a preferred embodiment the polyolefin composition (I) comprises 40 to 80 wt%, preferably 50 to 70 wt% of the heterophasic polymer composition (A) and 20 to 60 wt%, preferably 30 to 50 wt% of the polyethylene composition (B).
[0045] Preferably, the polyolefin composition (I) has at least one, more preferably all, of the following properties:
[0046] - a melt flow rate MFR (tot) of 0.001 to 5.0 g / 10 min measured according to method ISO 1133-2:2011 at 230°C and a load of 2.16 Kg; and / or
[0047] - Equal to or less than 1.00 g / cm2 as measured according to ASTM Standard D792–08 3 In one embodiment, the density is equal to or greater than 0.90 g / cm 3 ; and / or
[0048] - the tensile modulus measured on injection molded specimens according to method ISO 527-1:2012 is at least 100% higher, preferably at least 150% higher, still more preferably at least 200% higher than the tensile modulus of the heterophasic polymer composition (A). In one embodiment, the tensile modulus of the polyolefin composition (I) is less than 500% higher than the tensile modulus of the heterophasic polymer composition (A).
[0049] In one embodiment, the polyolefin composition (I) does not include any inorganic reinforcement, such as glass fibers or mineral fillers, and / or any fibrous reinforcement, such as polyolefin fibers or wool.
[0050] In one embodiment, the polyolefin composition (I) comprises only component (B) as reinforcing agent.
[0051] In the following, the individual components of the polyolefin composition (I) are defined in more detail. Said components may be comprised in the polyolefin composition (I) in any combination.
[0052] The α-olefin optionally included in components (a) and (b) of the heterophasic polymer composition (A) is preferably independently selected from the group consisting of butene-1, hexene-1, 4-methyl-1-pentene, octene-1 and combinations thereof, preferably the α-olefin is butene-1.
[0053] In one embodiment, component (a) of the heterophasic polymer composition (A) is a blend of propylene polymers.
[0054] In one embodiment, component (a) of the heterophasic polymer composition (A) is a propylene homopolymer or a blend of propylene homopolymers.
[0055] In a preferred embodiment, component (a) of the heterophasic polymer composition (A) has at least one, more preferably all, of the following properties:
[0056] - equal to or less than 5% by weight, preferably equal to or less than 3% by weight, of a fraction XS(a) soluble in xylene at a temperature of 25° C., based on the weight of (a). In one embodiment, for each upper limit, the lower limit is 0.1% by weight, based on the weight of (a); and / or
[0057] - a melt flow rate MFR(a) equal to or higher than 50 g / 10 min, preferably ranging from 50 to 300 g / 10 min, measured according to method ISO 1133-2:2011 at a temperature of 230°C and a load of 2.16 Kg.
[0058] In one embodiment, component (a) is a propylene homopolymer or a blend of propylene homopolymers having all of the above characteristics.
[0059] Component (b) is an ethylene copolymer or a blend of ethylene copolymers.
[0060] In one embodiment, component (b) of the heterophasic polymer composition (A) is a copolymer or a blend of copolymers of ethylene and 1-butene.
[0061] In a preferred embodiment, component (b) of the heterophasic polymer composition (A) has at least one, preferably all, of the following properties:
[0062] - a weight average molecular weight Mw measured by GPC of equal to or greater than 50,000 g / mol, preferably ranging from 50,000 to less than 1,000,000 g / mol; and / or
[0063] - equal to or greater than 40% by weight, preferably equal to or greater than 65% by weight, of the fraction XS(b) soluble in xylene at a temperature of 25° C., based on the weight of (b). In one embodiment, for each lower limit, the upper limit of the fraction XS(b) soluble in xylene at a temperature of 25° C. is equal to 100% by weight.
[0064] In one embodiment, the heterophasic polymer composition (A) preferably comprises:
[0065] (a) 35 to 70 wt.%, more preferably 40 to 65 wt.%, of at least one propylene polymer selected from the group consisting of propylene homopolymers, propylene with ethylene and / or at least one copolymer of the formula CH2=CHR 1 A copolymer of α-olefins, wherein R 1 is a linear or branched C2 to C8 alkyl group, the copolymer comprising up to and including 10.0 wt%, preferably from 0.05 to 8.0 wt%, based on the weight of (a), of units derived from ethylene and / or α-olefins;
[0066] (b) 15 to 40% by weight, more preferably 20 to 35% by weight, of at least one ethylene and at least one compound of the formula CH2=CHR 1 A copolymer of α-olefins, wherein R 1 is a linear or branched C2 to C8 alkyl group, the copolymer comprising from 10 to 40 wt%, preferably from 20 to 35 wt%, based on the weight of (b), of units derived from α-olefins; and
[0067] (c) 5 to 30% by weight, preferably 7 to 20% by weight, of at least one propylene and ethylene and / or at least one compound of the formula CH2=CHR 1 Copolymers of α-olefins and mixtures thereof, wherein R 1 is a linear or branched C2 to C8 alkyl group, the propylene copolymer comprises up to and including 50 wt%, preferably from 15 to 50 wt%, based on the weight of (c), of units derived from ethylene and / or α-olefins;
[0068] The amounts of components (a), (b) and (c) are based on the total weight of (a)+(b)+(c).
[0069] In a preferred embodiment the at least one propylene copolymer (c) is selected from propylene-ethylene copolymers.
[0070] The multiphase polymer composition (A) optionally comprises up to and including 3.0 wt. %, for example from 0.01 to 3.0 wt. %, of at least one additive (d) selected from the group consisting of antistatic agents, antioxidants, light stabilizers, slip agents, antacids, melt stabilizers and combinations thereof, wherein the amount of additive (d) is calculated on the total weight of the polyolefin composition including other additives (d), the total weight being 100%.
[0071] The heterophasic polymer composition (A) preferably has a melt flow rate MFR(A) equal to or greater than 8.0 g / 10 min, measured according to the method ISO 1133-2:2011 at a temperature of 230° C. and a load of 2.16 Kg. In an embodiment, the MFR(A) measured according to the method ISO 1133-2:2011 at a temperature of 230° C. and a load of 2.16 Kg is equal to or lower than 150 g / 10 min.
[0072] The heterophasic polymer composition (A) is a reactor blend or a melt blend or a combination thereof.
[0073] In one embodiment, the heterophasic polymer composition (A) is a reactor blend heterophasic polyolefin composition (A1 ), the heterophasic polyolefin composition (A1 ) comprising:
[0074] (a) 35 to 70 wt. %, preferably 40 to 65 wt. % of a propylene homopolymer;
[0075] (b) 15 to 40% by weight, preferably 20 to 35% by weight, of a copolymer of ethylene and 1-butene, the copolymer comprising from 10 to 40% by weight, preferably from 20 to 35% by weight, based on the weight of (b), of units derived from 1-butene,
[0076] (c) 5 to 30 wt%, preferably 7 to 25 wt%, of a copolymer of propylene and ethylene, the copolymer comprising up to and including 50 wt%, preferably from 15 to 50 wt%, based on the weight of (c), of units derived from ethylene; and
[0077] (d) optionally up to and including 3.0 wt. %, preferably from 0.01 wt. % to 3.0 wt. % of at least one additional additive selected from the group consisting of antistatic agents, antioxidants, light stabilizers, slip agents, antacids, melt stabilizers and combinations thereof,
[0078] The amounts of components (a), (b), (c) and (d) are calculated based on the total weight of (a)+(b)+(c)+(d), and the total weight is 100%.
[0079] The heterophasic polyolefin composition (A1) has at least one, preferably all, of the following properties:
[0080] - ranging from 30 to 50% by weight, based on the weight of (A1), of a fraction XS (A1) soluble in xylene at a temperature of 25° C.; and / or
[0081] - an intrinsic viscosity XSIV(A1) of the fraction soluble in xylene at 25° C. ranging from 1.50 to 3.00 dl / g, preferably from 2.00 to 2.50 dl / g; and / or
[0082] - a melt flow rate MFR(A1 ) ranging from 5 to 20 g / 10 min, preferably from 8 to 15 g / 10 min, measured according to method ISO 1133-2:201 1 at a temperature of 230°C and a load of 2.16 Kg.
[0083] The heterophasic polymer composition (A) is prepared by melt blending components (a), (b) and optionally (c) and (d), or by polymerizing the relevant monomers in at least two polymerization stages, wherein the second polymerization stage and each optional subsequent polymerization stage are carried out in the presence of the produced polymer and the catalyst used in the immediately preceding polymerization stage, thereby obtaining a reactor blend of components (a), (b) and optionally (c), and optionally melt blending the reactor blend thus obtained with component (d).
[0084] In one embodiment, the heterophasic polymer composition (A) is a reactor blend of components (a), (b), and optionally (c).
[0085] The monomers are polymerized in the presence of a catalyst selected from metallocene compounds, highly stereospecific Ziegler-Natta catalyst systems and combinations thereof, preferably in the presence of a highly stereospecific Ziegler-Natta catalyst system comprising:
[0086] (1) a solid catalyst component comprising a magnesium halide support and a stereoregular internal donor, wherein a Ti compound having at least one Ti-halogen bond is present on the magnesium halide support;
[0087] (2) optionally, but preferably, containing an Al promoter; and
[0088] (3) Optionally, but preferably, additional electron donor compounds (external donors).
[0089] The solid catalyst component (1) preferably comprises TiCl4 in an amount ensuring that from 0.5 to 10 wt% Ti is present relative to the total weight of the solid catalyst component (1).
[0090] The solid catalyst component (1) comprises at least one stereoregular internal electron donor compound selected from mono- or bidentate organic Lewis bases, preferably selected from esters, ketones, amines, amides, carbamates, carbonates, ethers, nitriles, alkoxysilanes and combinations thereof.
[0091] Preferred donors are esters of phthalic acid, such as those described in EP 45977 A2 and EP 395083 A2, in particular diisobutyl phthalate, di-n-butyl phthalate, di-n-octyl phthalate, diphenyl phthalate, benzyl butyl phthalate and combinations thereof.
[0092] The esters of aliphatic acids may also be selected from esters of malonic acid, such as those described in WO98 / 056830, WO98 / 056833, WO98 / 056834; esters of glutaric acid, such as those disclosed in WO00 / 55215; and esters of succinic acid, such as those disclosed in WO00 / 63261.
[0093] A specific type of diesters are those derived from the esterification of aliphatic or aromatic diols, such as those described in WO 2010 / 078494 and USP 7,388,061.
[0094] In some embodiments, the internal donor is selected from 1,3-diethers such as those described in EP361493, EP728769, and WO02 / 100904.
[0095] Internal donors, in particular specific mixtures of aliphatic or aromatic mono- or dicarboxylic acid esters and 1,3-diethers as disclosed in WO 07 / 57160 and WO 2011 / 061134, can be used as internal donors.
[0096] The preferred magnesium halide support is magnesium dihalide.
[0097] The amount of the internal donor to be held fixed on the solid catalyst component (1) is 5 to 20 mol% relative to the magnesium dihalide.
[0098] A preferred process for preparing the solid catalyst component (1) is described in EP 395 083 A2.
[0099] The preparation of catalyst components according to general methods is described, for example, in European patent applications US 4,399,054, US 4,469,648, WO 98 / 44009 A1 and EP 395 083 A2.
[0100] In some embodiments, the catalyst system comprises an Al-containing cocatalyst (2) selected from Al-trialkyl, preferably selected from the group consisting of Al-triethyl, Al-triisobutyl and Al-tri-n-butyl. The Al / Ti weight ratio in the catalyst system is from 1 to 1000, preferably from 20 to 800.
[0101] In an embodiment, the catalyst system comprises an additional electron donor compound (3) (external electron donor) selected from silicon compounds, ethers, esters, amines, heterocyclic compounds, in particular 2,2,6,6-tetramethylpiperidine, and ketones.
[0102] Preferred silicon compounds are selected from methylcyclohexyldimethoxysilane (C-donor), dicyclopentyldimethoxysilane (D-donor) and mixtures thereof.
[0103] The polymerization to obtain the individual components (a), (b) and optionally (c) or the sequential polymerization process to obtain the heterophasic polymer composition (A) can be carried out continuously or batchwise in the liquid or gas phase.
[0104] Liquid phase polymerization can be slurry, solution or bulk (liquid monomer).
[0105] The gas phase polymerization can be carried out in a fluidized bed or stirred fixed bed reactor or in a multizone circulation reactor, as described in EP1012195.
[0106] The reaction temperature is preferably comprised within the range of 40 to 90° C. and the polymerization pressure is from 3.3 to 4.3 MPa for a process in liquid phase and from 0.5 to 3.0 MPa for a process in gas phase.
[0107] Suitable polymerisation processes for producing the heterophasic polymer composition (A) are described in patent applications WO 03 / 051984 and WO 03 / 076511, the entire contents of which are incorporated herein by reference.
[0108] Composition (B) is a multimodal polyethylene composition comprising a UHMWPE fraction (i) and a PE-wax (ii).
[0109] In a preferred embodiment, the polyethylene composition (B) comprises at least 75 wt%, more preferably at least 80 wt% of (i) + (ii), wherein the amounts of (i) and (ii) are based on the total weight of the polyethylene composition (B), the total weight being 100%.
[0110] Preferably, the polyethylene composition (B) has a melt flow rate MFR(B) up to and including 10 g / 10 min, preferably ranging from 0.00001 to 10 g / 10 min, measured according to ISO 1133-2:2011 at 190°C and a load of 2.16 Kg.
[0111] The polyethylene composition (B) preferably comprises:
[0112] (i) 25 to 85 wt%, preferably 60 to 75 wt% of a polyethylene component having a weight average molecular weight Mw(i) equal to or greater than 1,000,000 g / mol as measured by gel permeation chromatography;
[0113] (ii) 10 to 65 wt%, preferably 10 to 20 wt% of a polyethylene component having a weight average molecular weight Mw(ii) equal to or lower than 5,000 g / mol as measured by gel permeation chromatography, and
[0114] (iii) up to and including 100% by weight of a polyethylene component other than component (i) and component (ii),
[0115] The polyethylene composition (B) comprises at least 70 wt%, preferably at least 75 wt%, more preferably at least 80 wt% of (i) + (ii), and the amounts of (i) and (ii) are calculated based on the total weight of the polyethylene composition (B), and the total weight is 100%.
[0116] Preferably, the polyethylene composition (B) has a value of Mw / Mn(B) equal to or greater than 300, preferably ranging from 300 to 1,500, wherein Mw and Mn are the weight average molecular weight and number average molecular weight of the polyethylene composition (B) measured by GPC, respectively.
[0117] The polyethylene components (i) to (iii) are independently selected from the group consisting of: ethylene homopolymers, ethylene and at least one of the formula CH2=CHR 1 Copolymers of α-olefins and mixtures thereof, wherein R 1 It is a straight chain or branched C2 to C8 alkyl group.
[0118] The α-olefin is preferably selected from the group consisting of butene-1, hexene-1, 4-methyl-1-pentene, octene-1, and combinations thereof.
[0119] In a preferred embodiment, the polyethylene components (i) to (iii) are ethylene homopolymers.
[0120] The density of polyethylene components (i) and (ii) measured according to method ASTM D 792-08 preferably ranges from 0.900 to 0.965 g / cm 3 , more preferably from 0.930 to 0.960 g / cm 3 .
[0121] Preferably, the polyethylene component (i) has at least one, preferably all, of the following properties:
[0122] - the molecular weight distribution MWD (i) has a GPC peak (1) comprised in the range from 1,000,000 to 3,000,000 g / mol, preferably from 1,500,000 to 3,000,000 g / mol, wherein MWD (i) is determined by gel permeation chromatography; and / or
[0123] - a Mw / Mn(i) value up to and including 5, preferably from 1.2 to 5, more preferably from 1.5 to 4.5, wherein Mn is the number average molecular weight measured by gel permeation chromatography.
[0124] The polyethylene component (ii) preferably has at least one, more preferably all, of the following properties:
[0125] - MWD (ii) has a GPC peak (2) comprised in the range from 500 to 1,500 g / mol, wherein MWD (ii) is determined by gel permeation chromatography; and / or
[0126] - a Mw / Mn(ii) value up to and including 5, preferably from 1.2 to 5, more preferably from 1.5 to 4.5, wherein Mn is the number average molecular weight measured by gel permeation chromatography.
[0127] More preferably, the polyethylene composition (B) is a multimodal polyethylene composition as defined previously, the MWD of which shows a GPC peak (1) comprised in the range from 1 ,000,000 to 3,000,000 g / mol, preferably from 1 ,500,000 to 3,000,000 g / mol and a GPC peak (2) comprised in the range from 500 to 1 ,500 g / mol.
[0128] As regards component (ii) of the present invention, the polyethylene components (i) to (iii) are preferably obtained by a polymerization process using a single site catalyst, as reported, for example, in WO01 / 021668 and WO2011 / 089017 for UHMWPE component (i) and in EP1188762 for polyethylene with low Mw values.
[0129] The polyethylene component (iii) is preferably obtained during a polymerisation process for preparing the polyethylene component (i) and / or the polyethylene component (ii).
[0130] The polyethylene component (i) is preferably prepared by polymerizing the relevant monomers using a polymerization catalyst comprising a cyclopentadienyl complex of chromium, preferably containing an η5-cyclopentadienyl moiety, especially [η 5 -3,4,5-trimethyl-1-(8-quinolyl)-2-trimethylsilyl-cyclopentadienyl]-chromium dichloride (CrQCp catalyst component).
[0131] The polyethylene component (ii) is preferably prepared by polymerizing the relevant monomers with a polymerization catalyst comprising a bis(imino)pyridine complex of chromium, preferably 2,6-bis-[1-(2,6-dimethylphenylimino)ethyl]pyridine chromium(III) trichloride (CrBIP catalyst component).
[0132] The catalyst components are preferably supported on a solid component. Preferably, a finely dispersed carrier is used, which can be any organic or inorganic solid. Examples are silica gel, magnesium chloride, aluminum oxide, mesoporous materials, aluminosilicates, hydrotalcites and organic polymers such as polyethylene, polypropylene, polystyrene, polytetrafluoroethylene or polymers with polar functional groups, for example copolymers of ethylene and acrylic acid esters, acrolein or vinyl acetate. The carrier material used preferably has a range of 10 to 1000 m 2 / g specific surface area, pore volume ranging from 0.1 to 5 ml / g and average particle size from 1 to 500 μm.
[0133] The preparation of supported catalysts is carried out by physical adsorption or by means of chemical reactions, ie by covalent bonding of the components to reactive groups on the surface of the support.
[0134] The catalyst components are preferably contacted with the support in a suitable solvent to give a soluble reaction product, adduct or mixture.
[0135] Suitable and preferred support materials, their preparation and their use for the preparation of supported catalysts are described in WO 2005 / 103096.
[0136] The catalyst components, particularly the CrQCp and CrBIP components, generally need to be contacted with an activator, preferably selected from aluminoxane and non-aluminoxane activators, to achieve high polymerization productivity.
[0137] Particularly useful aluminoxanes are open chain aluminoxane compounds of the general formula (1):
[0138]
[0139] Or a cyclic aluminoxane compound of the general formula (2):
[0140]
[0141] Where R 1 To R 4 are independently selected from C1 to C6 alkyl groups; preferably, R 1 To R 4 is independently selected from the group consisting of methyl, ethyl, n-butyl and isobutyl, and l is an integer from 1 to 40, preferably from 4 to 25.
[0142] Methylaluminoxane (MAO) is preferred.
[0143] Suitable non-aluminoxane activators include alkylaluminums, alkylaluminum halides, boron or aluminum anionic compounds, trialkylboron and triarylboron compounds, etc. Examples are triethylaluminum, trimethylaluminum, triisobutylaluminum, diethylaluminum chloride, lithium tetrakis(pentafluorophenyl)borate, triphenylcarbon tetrakis(pentafluorophenyl)borate, lithium tetrakis(pentafluorophenyl)aluminate, tris(pentafluorophenyl)boron and tris(pentabromophenyl)boron.
[0144] The activator is usually used in an amount ranging from 0.01 to 10,000, preferably from 1 to 5,000 moles per mole of the unit site catalyst.
[0145] During the preparation of the single site catalyst and / or pre-contact with the single site catalyst, they may be fed separately to the polymerization zone, supported on the aforementioned support.
[0146] In a preferred embodiment, polyethylene components (i) to (iii) are prepared in a single polymerization step by loading two single-site catalyst components, particularly CrQCp and CrBIP, on the same carrier, thereby obtaining a dual-site catalyst component that ensures that the catalyst centers are in relatively close spatial proximity, resulting in a fine mixing of the polyethylene components formed on each catalyst center.
[0147] Thus, in a preferred embodiment the polyethylene composition (B) is a reactor blend of polyethylene components (i) to (iii).
[0148] The relative amounts of polyethylene components (i) to (iii) reported previously were obtained by appropriately setting the relative amounts of the two single site catalyst components, in particular CrQCp and CrBIP, which would determine the amounts of components (i) to (iii) in the polyethylene composition (B).
[0149] In a preferred embodiment, the CrBIP / CrQCp molar ratio ranges from 0.1 to 20, more preferably from 0.3 to 10, in particular from 0.5 to 8.
[0150] In a less preferred alternative, the polyethylene components (i) to (iii) are produced separately by polymerising the relevant monomers in the presence of corresponding single site catalysts and the polyethylene composition (B) is prepared by melt mixing the individual components.
[0151] The polyethylene components (i) to (iii) are prepared by gas phase polymerization, in particular in a gas phase fluidized bed reactor, solution polymerization or suspension polymerization, in particular in a loop reactor and a stirred tank reactor. The gas phase polymerization can be carried out in a condensed or supercondensed manner, wherein part of the circulating gas is cooled below the dew point and recirculated to the reactor as a two-phase mixture.
[0152] Polyethylene components (i) to (iii) can also be produced in a gas phase reactor called a multi-zone circulation reactor (MZCR) with two interconnected polymerization zones. Polymer particles flow upward through a first polymerization zone named "riser" under fast fluidization or conveying conditions, leave the riser and enter a second polymerization zone named "downcomer", where they flow through the second polymerization zone in a densified form under gravity. A continuous circulation of polymer is established between the riser and the downcomer. Typically, fast fluidization conditions are established in the riser by feeding a gas mixture comprising the relevant monomers to the riser. The catalyst system is preferably fed into the reactor at any point in the riser.
[0153] In a multi-zone circulation reactor, two polymerization zones with different compositions can be obtained by feeding a gas / liquid stream (barrier stream) to the upper part of the downcomer. The gas / liquid stream acts as a barrier to the gas phase from the riser and can establish an upward net gas flow in the upper part of the downcomer. The upward gas flow established has the effect of preventing the gas mixture present in the riser from entering the downcomer. Such a reactor is described, for example, in WO 97 / 04015.
[0154] If desired, different or identical polymerization zones can also be connected in series to form a polymerization cascade, as for example in a Hallstaron. In the process. A parallel reactor arrangement using two or more identical or different processes is also possible. In addition, molar mass regulators (for example hydrogen) or conventional additives (such as antistatic agents) can also be used in the polymerization.
[0155] The polymerization temperature is typically in the range from -20°C to 115°C, and the pressure is typically in the range from 1 to 100 bar.
[0156] In the case of suspension polymerization, the suspension medium is preferably an inert hydrocarbon such as isobutane or a mixture of hydrocarbons or the monomers themselves. The solids content of the suspension is generally in the range of from 10 to 80%. The polymerization can be carried out batchwise (for example in a stirred autoclave) or continuously (for example in a tubular reactor, preferably in a loop reactor).
[0157] In one embodiment, the polyethylene composition (B) comprises at least one additional additive (iv) used in the relevant technical field, preferably selected from the group consisting of: processing stabilizers, light stabilizers, heat stabilizers, lubricants, antioxidants, antiblocking agents, antistatic agents, pigments, dyes and mixtures thereof. The additive is included in the polyethylene composition (B) in an amount of up to and including 6 wt%, preferably from 0.1 to 1 wt%, based on the total weight of the polyethylene composition (B) including the additive, the total weight being 100%.
[0158] In a preferred embodiment the polyethylene composition (B) does not comprise any polymer other than polyethylene.
[0159] In a further embodiment, the polyethylene composition (B) consists of the polyethylene components (i) to (iii) and optionally further additives (iv).
[0160] In one embodiment, the polyolefin composition (I) optionally comprises up to and including 40 wt%, preferably 0.5 to 30 wt%, more preferably 1 to 20 wt% of an additional component (C) selected from the group consisting of:
[0161] (C1) enhancer;
[0162] (C2) a saturated or unsaturated styrene or α-methylstyrene block copolymer, preferably comprising up to and including 30 wt. % polystyrene, more preferably from 10 wt. % to 30 wt. % based on the weight of (C2);
[0163] (C3) polyolefins functionalized with a compound selected from the group consisting of maleic anhydride, C1 to C10 linear or branched dialkyl maleates, C1 to C10 linear or branched dialkyl fumarates, itaconic anhydride, C1 to C10 linear or branched itaconic acid, dialkyl esters, maleic acid, fumaric acid, itaconic acid;
[0164] (C4) additives selected from the group consisting of pigments, dyes, extender oils, flame retardants, anti-UV agents, UV stabilizers, lubricants, anti-blocking agents, slip agents, waxes;
[0165] (C5) Their combination,
[0166] The amount of the additional component (C) is based on the total weight of (A)+(B)+(C), and the total weight is 100%.
[0167] The reinforcing agent (C1) is preferably an inorganic reinforcing agent selected from the group consisting of inorganic fibers (such as glass fibers), mineral fillers (such as talc), and combinations thereof. Preferably, the reinforcing agent (C1) is glass fibers.
[0168] The saturated or unsaturated styrene or alpha-methylstyrene block copolymer (C2) preferably comprises from 10 to 30 wt.% of styrene, based on the weight of (C2). Preferably, (C2) is a styrene block copolymer selected from the group consisting of polystyrene-polybutadiene-polystyrene (SBS), polystyrene-poly(ethylene-butylene)-polystyrene (SEBS), polystyrene-poly(ethylene-propylene)-polystyrene (SEPS), polystyrene-polyisoprene-polystyrene (SIS), polystyrene-poly(isoprene-butadiene)-polystyrene (SIBS) and mixtures thereof. More preferably, the styrene block copolymer (C2) is polystyrene-poly(ethylene-butylene)-polystyrene (SEBS).
[0169] The styrene block copolymer (C2) preferably has at least one, preferably all, of the following properties:
[0170] - a melt flow rate (MFR) measured according to ASTM D1238 (230°C, 2.16 Kg) ranging from 5 to 80 g / 10 min, preferably from 10 to 60 g / 10 min, more preferably from 10 to 30 g / 10 min; and / or
[0171] - A Shore A value measured according to ASTM 2240 (30 seconds) equal to or lower than 70, preferably ranging from 30 to 70, more preferably from 30 to 60.
[0172] Styrene or α-methylstyrene block copolymers (C2) are prepared by ionic polymerization of the relevant monomers and are available under the trade name Kraton TM Commercially available and sold by Kraton Polymers.
[0173] The functionalized polyolefin (C3) is preferably selected from polyethylene, polypropylene and mixtures thereof, which are functionalized with a compound selected from the group consisting of maleic anhydride, C1 to C10 linear or branched dialkyl maleates, C1 to C10 linear or branched dialkyl fumarates, itaconic anhydride, C1 to C10 linear or branched itaconic acid, dialkyl esters, maleic acid, fumaric acid, itaconic acid and mixtures thereof.
[0174] In a preferred embodiment, the functionalized polyolefin (C3) is polyethylene and / or polypropylene grafted with maleic anhydride (MAH-g-PP and / or MAH-g-PE).
[0175] Functionalized polyolefins are known in the art and can be produced by functionalization processes carried out in solution, in the solid state or preferably in the melt, for example, by reactive extrusion of the polymer in the presence of a grafting compound and a free radical initiator. For example, the functionalization of polypropylene and / or polyethylene with maleic anhydride is described in EP0572028A1.
[0176] An example of a functionalized polyolefin is the commercially available Amplify TM TY, ExxonMobil Chemical Company's Exxelor TM 、Byk (Altana Group) TPPP, Polyram Group and Chemtura and combinations thereof.
[0177] The polyolefin composition (I) is produced by intimately mixing components (A), (B) and optionally (C) using methods and equipment known in the art, for example by compounding the components at a temperature of 180 to 220°C.
[0178] It has been found that by molding the polyolefin composition (I) under appropriate conditions, the tensile properties of the heterophasic polymer composition (A) are improved due to the flow induced reinforcement effect of the polyethylene composition (B).
[0179] Therefore, the present disclosure also relates to a process for manufacturing a shaped article, the method comprising subjecting the flow rate of the molten polyolefin composition (I) as described above to a temperature equal to or greater than 50 s. -1 , preferably equal to or greater than 150s -1 The shear rate steps.
[0180] In one embodiment, the flow rate of the molten polyolefin composition (I) is subjected to a flow rate of equal to or greater than 3 s. -1 , preferably equal to or greater than 8s -1 The strain rate.
[0181] The manufacturing process preferably comprises:
[0182] - melting the polyolefin composition (I) as described above at a temperature equal to or greater than 180°C, preferably ranging from 180°C to 220°C;
[0183] - subjecting the flow rate of the molten polyolefin composition (I) to a flow rate of equal to or greater than 50 s -1 , preferably equal to or greater than 150s-1 The shear rate; and
[0184] - Shaping and cooling the molten polyolefin composition (I).
[0185] The flow rate of the molten polyolefin composition (I) is subjected to a temperature of equal to or greater than 50 s. -1 The step of increasing the shear rate is preferably carried out by injection molding or by an extrusion-based process.
[0186] In a preferred embodiment, the flow rate of the molten polyolefin composition (I) is subjected to a flow rate of equal to or greater than 50 s. -1 The shear rate steps were performed by injection molding, and the shear rate ranged from 50 to 3,000 s -1 , preferably from 200 to 2,000s -1 .
[0187] In one embodiment, in the injection molding process, the flow rate of the molten polyolefin composition (I) as described above is subjected to a flow rate ranging from 3 to 200 s. -1 , preferably from 8 to 120s -1 The strain rate.
[0188] The injection molding process is advantageously carried out by melt mixing the polyolefin composition (I) in a conventional twin-screw extruder, preferably a conventional twin-screw co-rotating extruder.
[0189] The components of the polyolefin composition (I) are fed into the injection molding machine individually or preferably premixed, more preferably intimately premixed in the molten state. Premixing in the molten state is preferably accomplished by compounding the components of the polyolefin composition (I) in a compounder of the type used in the related art.
[0190] The extrusion-based process is preferably an extrusion-based 3D printing process, wherein the flow rate of the molten polyolefin composition (I) is subjected to a flow rate of equal to or greater than 50 s. -1 The shear rate steps were performed by extrusion-based 3D printing, and the shear rate ranged from 50 to 1,000 s -1 , preferably from 100 to 600s -1 .
[0191] In a preferred embodiment, the extrusion-based 3D printing process comprises subjecting the flow rate of the molten polyolefin composition (I) to a temperature ranging from 3 to 50 s. -1 , preferably from 3 to 20s -1 The strain rate.
[0192] The 3D printing process is preferably a fused filament fabrication (FFF) process, also known as fused deposition modeling (FDM), performed using a commercially available extrusion-based 3D printer.
[0193] The components of the polyolefin composition (I) are fed into the 3D printer individually or preferably premixed, more preferably intimately premixed in the molten state. Premixing in the molten state is preferably accomplished by compounding the components of the polyolefin composition (I) in a compounder of the type used in the related art.
[0194] In another aspect, the present disclosure relates to a filament for extrusion-based 3D printing (also referred to as extrusion-based additive manufacturing), the filament comprising or consisting of the polyolefin composition (I) as disclosed above.
[0195] The shaped articles obtained by the manufacturing process according to the present disclosure have excellent mechanical properties with a significantly reduced density compared to the heterophasic polymer composition (A) reinforced only with conventional inorganic fillers, such as glass fibers.
[0196] In another aspect, the present disclosure relates to the use of the polyethylene composition (B) as described above as a reinforcement masterbatch for the heterophasic polymer composition (A) as described above.
[0197] The method of using the polyolefin composition (B) to reinforce the heterophasic polymer composition (A) comprises:
[0198] - adding 20 to 85 wt%, preferably 20 to 60 wt%, more preferably 30 to 50 wt% of the polyethylene composition (B) to 15 to 80 wt%, preferably 40 to 80 wt%, more preferably 50 to 70 wt% of the heterophasic polymer composition (A) to obtain the polyolefin composition (I), wherein the amounts of (A) and (B) are based on the total weight of (A) + (B);
[0199] The polyolefin composition (I) is preferably melted at a temperature equal to or greater than 180° C. and the flow rate of the molten polyolefin composition (I) is subjected to a temperature equal to or greater than 50 s. -1 , preferably equal to or greater than 150s -1 The shear rate; and
[0200] - Shaping and cooling the molten polyolefin composition (I).
[0201] In the above method, the step of cooling the molten polyolefin composition preferably comprises shaping the polyolefin composition by an extrusion-based process or by injection. More preferably, the extrusion-based process is 3D printing.
[0202] The features describing the subject matter of the present disclosure are not inseparably linked to each other. Therefore, the preference of a particular level of a feature does not necessarily involve the preference of the same level of the remaining features of the same or different components. It is intended in the present disclosure that any preferred range of the features of the components (A) and (B) from which the polyolefin composition (I) is obtained can be combined independently of the preference level, and components (A) and (B) can be combined with any possible additional components and features thereof described in the present disclosure.
[0203] Examples
[0204] The following examples are illustrative only and are not intended to limit the scope of the present disclosure in any way.
[0205] Characterization methods
[0206] The following method was used to determine the properties indicated in the specification, claims, and examples.
[0207] Melt flow rate: determined according to method ISO 1133-2:2011 at a temperature of 230°C or 190°C (depending on the polymer) and a load of 2.16 Kg. The melt flow rate (MFR(tot)) of the composition is related to the melt flow rates of the components by the following formula:
[0208]
[0209] in
[0210] w(i) is the weight fraction of component i in the composition, and MFR(i) is the melt flow rate of component i.
[0211] Density: Measured according to method ASTM D 792-08.
[0212] Solubility in xylene at 25°C: 2.5g polymer sample and 250ml xylene are introduced into a glass flask equipped with a refrigerator and a magnetic stirrer. The temperature is raised to 135°C in 30 minutes. The resulting clear solution is kept under reflux and stirred for another 30 minutes. The solution is cooled in two stages. In the first stage, the temperature is reduced to 100°C in air under stirring for 10 to 15 minutes. In the second stage, the flask is transferred to a thermostatically controlled water bath at 25°C for 30 minutes. The temperature is reduced to 25°C without stirring during the first 20 minutes, and maintained at 25°C in the latter 10 minutes under stirring. The formed solid is filtered on a fast filter paper (e.g., Whatman filter paper grade 4 or 541). 100ml of the filtered solution (S1) is poured into a pre-weighed aluminum container, which is heated to 140°C on a heating plate under a nitrogen stream to remove the solvent by evaporation. The container was then kept in an oven at 80°C under vacuum until constant weight was reached. The amount of polymer soluble in xylene at 25°C was then calculated.
[0213] The xylene soluble fraction (XS(tot)) of a composition is related to the xylene soluble fraction of a component by the following formula:
[0214]
[0215] wherein w(i) is the weight fraction of component i in the composition and XS(i) is the xylene soluble fraction of component i.
[0216] C2 and C4 content in polymers containing C3, C2 and C4: 13 C NMR spectra were acquired on a Bruker AV-600 spectrometer equipped with a cryoprobe, operating at 120 °C in Fourier transform mode at 160.91 MHz. S δδ The peak of carbon (nomenclature according to "Monomer sequence distribution in ethylene-propylene rubber measured by 13C NMR. 3. Use of reaction probability model" CJ Carman, RA Harrington and CE Wilkes, Macromolecules, 1977, 10, 536) was used as an internal reference.
[0217] About 30 mg of sample was dissolved in 0.5 ml of 1,1,2,2-tetrachloroethane-d2 at 120°C, and 0.1 mg / ml of Irganox 1010 (AO1010) was added as an antioxidant. Each spectrum was acquired with a 90° pulse and a 15 second delay between pulse and CPD to remove 1H-13C coupling. 512 transients were stored in 65K data points using a spectral window of 9000 Hz. The triplet distribution was performed using the following equation (taking into account possible overlap with peaks originating from AO1010):
[0218] PPP=100I 19 / Σ PPE=100I 13 / Σ EPE=100I 11 / Σ
[0219] BBB=100I8 / Σ BBE=100I7 / Σ EBE=100I3 / Σ
[0220] XEX=100I 21 / Σ XEE=100(I 6+ I 10 ) / Σ
[0221] EEE=100(0.5I 17 +0.25(I 16 +I 15 )) / Σ
[0222] where Σ=I 19 +I 13 +I 11 +I8+I7+I 3+ I 21 +I 6+ I 10 +0.5I 17 +0.25(I 16 +I 15 ), Ii is the area of the corresponding carbon reported in the table below, and X is propylene or butene-1.
[0223]
[0224]
[0225] The molar contents of ethylene, propylene and butene-1 were calculated from the triplets using the following equations:
[0226] [E]mol%=EEE+XEE+XEX
[0227] [P] mol% = PPP + PPE + EPE
[0228] [B] mol% = BBB + BBE + EBE
[0229] The molecular weight of the monomers was used to convert the molar content to weight content.
[0230] C2 and C3 in polymers containing propylene and ethylene: 13 C NMR spectra were acquired on a Bruker AV-600 spectrometer equipped with a cryoprobe, operating at 120 °C in Fourier transform mode at 160.91 MHz. S δδ The peak of carbon (nomenclature according to "Monomer sequence distribution in ethylene-propylene rubber measured by 13C NMR. 3. Use of reaction probability model" CJ Carman, RA Harrington and CE Wilkes, Macromolecules, 1977, 10, 536) was used as an internal reference.
[0231] About 30 mg of sample was dissolved in 0.5 ml of 1,1,2,2-tetrachloroethane-d2 at 120 ° C, and 0.1 mg / ml of Irganox 1010 (AO1010) was added as an antioxidant. Each spectrum was acquired with a 90 ° pulse, a 15 second delay between pulse and CPD to remove 1H-13C coupling. 512 transients were stored in 32K data points using a spectral window of 9000 Hz. According to M. Kakugo, Y. Naito, K. Mizunuma and T. Miyatake, Macromolecules 1982, 15, 4, 1150 to 1152, the following equations (taking into account the possible overlap with the peaks derived from AO1010) were used for the assignment of spectra, triplet distribution and composition evaluation:
[0232] PPP=100T ββ / S PPE=100T βδ / S EPE=100T δδ / S
[0233] PEP=100s ββ / S PEE=100S βδ / S EEE=100(0.25S γδ +0.5S δδ ) / S
[0234] S=T ββ +T βδ +T δδ +S ββ +S βδ +0.25S γδ +0.5S δδ
[0235] The molar contents of ethylene and propylene were calculated from the ternary groups using the following equations:
[0236] [E]mol=EEE+PEE+PEP
[0237] [P]mol=PPP+PPE+EPE
[0238] The molecular weight of the monomers was used to convert the molar content to weight content.
[0239] Molecular weight properties: Average molecular weights Mw and Mn and molecular weight distribution were determined by gel permeation chromatography (GPC) on a PL-220 high temperature gel permeation chromatograph (Agilent HT-GPC) equipped with three PLGel Olexis columns and a triple detection system (differential refractive index detector, differential viscometer 210R (Viskotek), small angle light scattering). The column was calibrated using 12 monodisperse polystyrene standards (Agilent Technologies) with narrow molecular weight distributions ranging from 580 g / mol to 11,600,000 g / mol. The calibration curve was adapted to polyethylene by the universal calibration method (Grubisic Z., Rempp P and Benoit H., J. Polymer Sci., 5, 753 (1967)). The Mark-Houwing parameters kPS=0.000121 dl / g, αPS=0.706 for polystyrene and kPE=0.000406 dl / g, αPE=0.725 for polyethylene are valid in TCB at 135°C. Data recording, calibration and calculation were performed using NTGPC_Control_V6.02.03 and NTGPC_V6.4.24 (hs GmbH, Hauptstrasse 36, D-55437 Ober-Hilbersheim, Germany), respectively. Sample measurements were performed at 160°C in 1,2,4-trichlorobenzene (stabilized with 0.2 wt% of 2,6-di-tert-butyl-4-methylphenol (BHT)) at a flow rate of 1.0 mL / min, an injection volume of 500 μL and a polymer concentration of 0.01 wt% to 0.05 wt%.
[0240] Injection molding of test specimens: Tensile and impact test specimens were prepared by injection molding the compositions using a DSM Xplore micro-compounder 5cc equipped with an injection molding system DSMXplore 10cc at 220°C, 0.8 MPa and a holding pressure of 8 seconds. The mold temperature was 60°C.
[0241] Compression molding: Plates 110×80×2 and 4 mm were obtained with a compression molding system Collin 200P operating at 200°C, 0.8 MPa with a holding time of 20 minutes. Tensile test specimens of ISO 527-2:2012, type 5A geometry were cut from the 2 mm thick plates. Impact test specimens of ISO 179-1 / 1eA were cut from the 4 mm thick plates.
[0242] Tensile properties at break: Tensile modulus and tensile strength were measured according to method ISO 527-1:2012 with a tensile testing machine ZWICK Z005, makroXtens extensometer (load cell 2.5 kN). Six test specimens of ISO 527-2:2012, geometry type 5A were tested for each composition, with a pulling speed of 50 mm / min. The data were evaluated with the software TESTXPERT II V3.31. The average of the six measurements was taken as the value of the tested property.
[0243] Impact test: measured according to method ISO 179-1:2010 (notched impact at 23°C) with an impact tester Zwick 5102.100 / 00 pendulum impact tester on test specimens ISO 179-1 / 1eA. Five test specimens were tested for each composition. After determining the cross-sectional area at the notch, all specimens were impacted. The characteristics of the impact test are determined by the dissipated energy. The average of the five measurements is taken as the value for the impact resistance test.
[0244] Shear rate: The shear rate applied to the polymer melt during extrusion Calculated by the following formula:
[0245]
[0246] Where R L Indicates the radius of the die or nozzle (in mm) and is the volume flow rate of the polymer (unit: mm 3 / s). Measure the volume flow rate for a specific combination of 3D printer, nozzle diameter, temperature and printing speed (i.e. extrusion speed) For this purpose, the polymer throughput was measured gravimetrically. (unit: g / s) and divided by the polymer melt density ρ (unit: g / mm 3 ):
[0247] Strain rate: The rate of strain applied to the polymer melt during extrusion Calculated by the following formula:
[0248]
[0249] in is the volume flow rate of the polymer (unit: mm 3 / s), L indicates the length of the convergence zone of the die or nozzle (unit: mm), R L Indicates the radius of the die or nozzle at the outlet of the convergence zone (in mm), and R0 indicates the radius of the die or nozzle at the inlet of the convergence zone (in mm). Measures the volume flow rate for a specific combination of 3D printer, nozzle diameter, temperature, and printing speed (i.e., extrusion speed) For this purpose, the polymer throughput was measured gravimetrically. (unit: g / s) and divided by the polymer melt density ρ (unit: g / mm 3 ):
[0250] raw material:
[0251] HECO-1 - a heterophasic polymer comprising (by total weight of (a)+(b)+(c)):
[0252] (a) 56.5 wt% of a propylene homopolymer having, based on the weight of (a), a xylene soluble fraction XS(a) of 3 wt% and an MFR(a) of 70 g / 10 min (ISO 1133-2:2011, 230°C / 2.16 Kg);
[0253] (b) 23.0% by weight of a copolymer of ethylene and butene-1, the copolymer containing 27.4% by weight of units derived from butene-1, based on the weight of (b);
[0254] (c) 20.5 wt% of a propylene-ethylene copolymer containing 41.5 wt% of ethylene-derived units, based on the weight of (c).
[0255] HECO-1 is a reactor blend of components (a), (b) and (c) obtained as described in Examples 1 to 3 of patent application WO03 / 076511A1, the reactor blend having the following properties:
[0256] 35.2% by weight of fraction XS (HECO-1) soluble in xylene at a temperature of 25° C.;
[0257] - intrinsic viscosity XSIV (HECO-1) of the fraction soluble in xylene at 25° C. of 2.26 dl / g;
[0258] - a melt flow rate MFR (HECO-1) of 12.5 g / 10 min, measured according to method ISO 1133 at a temperature of 230° C. and a load of 2.16 Kg; and
[0259] - 25.2 wt.-% total ethylene content and 6.3 wt.-% total butene-1 content, based on the weight of (a)+(b)+(c).
[0260] The amounts of (a), (b) and (c) correspond to the splits of the reactor; the amount of ethylene in components b) and c) and the amount of butene-1 in component (c) are calculated from the total amount of ethylene C2 (tot) and butene-1 C4 (tot) measured on HECO-1 using the following formula:
[0261] C2(tot)=w(b)C2(b)+w(c)C2(c)
[0262] C4(tot)=w(b)C4(b)
[0263] C2(b)=100-w(b)C4(b)
[0264] wherein w(b) and w(c) are the weight fractions of components (b) and (c) in HECO-1, C2(b) and C2(c) are the amounts of ethylene in components (b) and (c), and C4(b) is the amount of butene-1 in component (b).
[0265] Component B : A polyethylene composition was prepared as described for composition II-2 in patent application WO2020 / 169423A1.
[0266] 2,6-Bis-[1-(2,6-dimethylphenylimino)ethyl]pyridinium chromium(III) chloride (CrBIP) was synthesized according to Esteruelas MA et al., Organometallics 2003; 22(3): 395-406. 5 -3,4,5-trimethyl-1-(8-quinolyl)-2-trimethylsilyl-cyclopentadienyl]-chromium dichloride (CrQCp): Enders et al. Organometallics 2004;23(16):3832–9, and Fernández et al. Organometallics 2007;26(18):4402–12.
[0267] Preparation of mixed catalyst system
[0268] will show a pore volume of 1.5 ml / g and 400 m 2 g -1A mesoporous silica catalyst support (Sylopol XPO2107 from Grace) with a specific surface area of 1.37 W was prepared in a Schlenk tube at 160 °C under high vacuum (10 -3 The suspension was dried in 4% bar for 14 hours. 20 mL of toluene was added and the suspension was sonicated for 10 minutes. After adding the calculated amount of MAO (Al:Cr=300:1), the mixture was stirred for 30 minutes and sonicated for 5 minutes. After settling, the MAO-treated catalyst support was washed with anhydrous toluene by removing and exchanging the supernatant. CrBIP was dissolved in toluene (0.2 mg mL -1 ) was pretreated with trimethylaluminum (TMA, 10 equiv.) and added via syringe. After stirring for 5 min, a toluene solution of CrQCp (0.2 mg mL -1 ) and the mixture was stirred again for 5 minutes. The CrBIP / CrQCp molar ratio was 3.0. After sedimentation, the activated catalyst was collected in n-heptane (20 mL), transferred to a reactor and polymerization was started. Ethylene polymerization was carried out in a 2.6L steel reactor (HITEC ZANG) equipped with a mechanical stirrer, a thermostat and a software interface. Therefore, the reactor was heated at 90°C in a high vacuum for 2 hours, filled with n-heptane (580 mL) and triisobutylaluminum (TiBAl, 3 mL, 1M in n-hexane) and saturated with ethylene (5 bar). After the prepared catalyst was transferred to the reactor, polymerization was carried out at 40°C, an ethylene pressure of 5 bar and a stirring speed of 200 rpm for 120 minutes. The polymer was stabilized with a methanol solution of BHT (2,6-di-tert-butyl-4-methylphenol), filtered and dried under reduced pressure at 60°C to constant weight.
[0269] The properties of the polyethylene compositions are reported in Table 1.
[0270] Table 1
[0271]
[0272] HECO-2 (Comparative)—A heterophasic polyolefin composition comprising:
[0273] (a) 60% by weight of a propylene homopolymer;
[0274] (b) 40 wt% of a propylene-ethylene copolymer containing 68 wt% ethylene, based on the weight of (b).
[0275] HECO-2 is a reactor blend of components (a) and (b) obtained as described in Examples 1 to 2 of patent application WO2005 / 014715 and has the following properties:
[0276] 31.2% by weight of fraction XS (HECO-2) soluble in xylene at a temperature of 25° C.;
[0277] - intrinsic viscosity XSIV (HECO-2) of the fraction soluble in xylene at 25° C. of 2.29 dl / g; and
[0278] - Melt flow rate MFR (HECO-1) of 11.3 g / 10 min, measured according to method ISO 1133 at a temperature of 230°C and a load of 2.16 Kg.
[0279] The amount of ethylene C2(b) in component (b) is calculated from the total amount of ethylene C2 (tot) measured on HECO-2 using the following formula:
[0280] C2(tot)=w(b)C2(b)wherein w(b) is the weight fraction of component (b) in HECO-2, C2(b) and C2(b) is the amount of ethylene in component (b).
[0281] Metocene MF650Y - A propylene homopolymer supplied by LyondellBasell with a very narrow molecular weight distribution and a MFR of 1800 g / 10 min (ISO 1133, 230°C / 2.16 Kg).
[0282] Kraton from Kraton Corporation TM G1657 V, a linear styrene triblock copolymer based on styrene and ethylene / butylene containing 13 wt% polystyrene, having an MFR (ASTM D1238; 230°C, 5 Kg) of 22 g / 10 min and a Shore A value (ASTM D2240, 10 sec) of 47.
[0283] From Dow Engage 7467 , containing 31% by weight of units derived from butene-1 and having a carbonyl content of 0.862 g / cm 3 Ethylene-butene copolymer with a density (ASTM D792) and a melt index (ASTM D1238, 190°C / 2.16Kg).
[0284] Polybond 3200 - Supplied by SI Group, maleic anhydride modified polypropylene homopolymer with maleic anhydride content ranging from 0.8 to 1.2 wt% (ASTM D6047) and MFR of 115 g / 10 min (ASTM D1238, 190°C / 2.16 Kg).
[0285] Moplen HP500N- A propylene homopolymer supplied by LyondellBasell having a MFR of 12 g / 10 min, measured according to method ISO 1133 at a temperature of 230°C and a load of 2.16 Kg.
[0286] GF - Glass fiber ThermoFlow 636EC10 from Johns Manville (diameter: 10 μm; length: 4 mm).
[0287] Additive Package Consists of 5.0 wt% Irgafos 168 (BASF), tris(2,4-di-tert-butylphenyl)phosphite, 7.5 wt% Irganox 1076 (BASF), octadecyl-3-[3,5-di-tert-butyl-4-hydroxyphenyl]propionate, 2.5 wt% Tinuvin 622 (BASF), an oligomeric hindered amine light stabilizer, 12.5 wt% talc, 25 wt% polydimethylsiloxane, 2.5 wt% magnesium oxide and 45 wt% Moplen HF501N (LyondellBasell), wherein the amounts are based on the weight of the additive package.
[0288] Example E1 and Comparative Examples CE2 to CE5
[0289] The components were melt mixed, pelletized and injection molded in a DSM Xplore compounder 5cc at 200°C, 120 rpm and 90 seconds hold time.
[0290] The composition of the test specimens and the test results of tensile and impact properties are shown in Table 2.
[0291] Table 2
[0292]
[0293]
[0294] Examples E6 to E9 and Comparative Examples CE10 and CE11
[0295] The components were melt mixed and pelletized in a DSM Xplore compounder 5cc at 200°C, 120 rpm and 90 seconds holding time. The pellets were injection molded into test specimens. The composition of the test specimens and the test results of tensile and impact properties are shown in Table 3.
[0296] Table 3
[0297]
[0298] Comparative Examples CE12 and CE13
[0299] The components were melt mixed and pelletized in a DSM Xplore compounder 5cc at 200°C, 120 rpm and 90 seconds holding time. Test specimens were obtained by compression molding the pellets. The composition and test results of the test specimens are shown in Table 4 and Table 4a.
[0300] Table 4
[0301]
[0302]
[0303] Table 4a
[0304] CE12 CE13 Tensile modulus MPa 400 600 Tensile Strength MPa 16.9 19.0 Notched Charpy Impact Strength <![CDATA[KJ / m 2 ]]> 46.0 32.0 density <![CDATA[g / cm 2 ]]> 0.90 0.93
[0305] Example E14 and Comparative Example CE15
[0306] The compositions of Example E8 and Comparative Example CE10 were subjected to four cycles of pelletizing and injection molding processes in a DSM Xplore microcompounder 5cc equipped with an injection molding system DSM Xplore 10cc at 220°C, 0.8 MPa and a holding pressure of 8 seconds (60°C mold temperature).
[0307] The values of tensile modulus and tensile strength measured at the end of each process cycle are shown in Table 5.
[0308] Table 5
[0309]
[0310] Examples E16 to E18 and Comparative Examples CE19 to CE21
[0311] Pellets of the composition produced in Example E8 and the composition produced in Example CE10 were extruded on a twin-screw extruder COLLIN TEACH-LINE™ ZK 25T with a circular die (3.00 mm diameter) to obtain filaments for 3D printing. The extrusion parameters are listed in Table 6. The extruded filaments were water cooled and wound on a printer roll.
[0312] Table 6
[0313] parameter <![CDATA[T 区1 [℃]]]> 190 <![CDATA[T 区2 [℃]]]> 190 <![CDATA[T 区3 [℃]]]> 180 <![CDATA[T 区4 [℃]]]> 175 Speed [number / min] 20 Feed rate [kg / h] 2.0 Output [mm / s] 60
[0314] 3D printed parts were produced with an Ultimaker 2+ FFF printer using 100% infill and a 0.8 mm diameter nozzle. The printing parameters are given in Table 7.
[0315] Table 7
[0316] Material Print base material Scotch tape Nozzle diameter [mm] 0.8 Line width [mm] 0.7 Floor height [mm] 0.2 Nozzle temperature [℃] 210 Printing plate temperature [℃] 60 Printer speed [mm / s] 25, 100 or 150 Fill Pattern Wire
[0317] Specimens for tensile testing and for Charpy impact testing were prepared by 3D printing filaments with the infill pattern oriented parallel to the longest dimension of the test specimen, corresponding to a 0° orientation with respect to the tensile / impact direction.
[0318] The values of tensile modulus and tensile strength measured for each printing / extrusion speed and the associated shear and strain rates to which the polymer melt was subjected in the process are shown in Table 8.
[0319] Table 8
[0320] E16 E17 E18 CE19 CE20 CE21 Print speed mm / s 25 100 150 25 100 150 Shear rate 1 / s 110 260 450 - - - Strain rate 1 / s 4.4 10.9 18.3 - - - Tensile modulus MPa 710 1,500 2,200 2,340 2,250 2,120 Tensile Strength MPa 20.1 29.2 79.0 28.9 28.2 26.6 Notched Charpy Impact Strength <![CDATA[kJ / m 2 ]]> 41 47 51 37 37 34
Claims
1. A polyolefin composition (I), comprising: (A) 15 to 80 weight percent of a heterophasic polymer composition comprising: (a) 50 to 80 wt% of at least one propylene polymer selected from the group consisting of a propylene homopolymer, a propylene and ethylene polymer and / or at least one copolymer of the formula CH2=CHR 1 Copolymers of α-olefins and mixtures thereof, wherein R 1 is a linear or branched C2 to C8 alkyl group, the copolymer comprising up to and including 10.0 wt% of units derived from ethylene and / or the α-olefin, based on the weight of (a); (b) 20 to 50% by weight of ethylene and at least one compound of the formula CH2=CHR 1 At least one copolymer of an α-olefin, wherein R 1 is a linear or branched C2 to C8 alkyl group, the copolymer comprises from 10 to 40% by weight of units derived from the α-olefin, based on the weight of (b), wherein the amounts of components (a) and (b) are based on the total weight of (a) + (b); (B) 20 to 85 wt% of a polyethylene composition comprising: (i) 25 to 85 wt.% of a polyethylene component having a weight average molecular weight Mw(i) equal to or higher than 1,000,000 g / mol as measured by gel permeation chromatography; (ii) 10 to 65% by weight of a polyethylene component having a weight average molecular weight Mw(ii) equal to or lower than 5,000 g / mol as measured by gel permeation chromatography, wherein the polyethylene composition (B) comprises at least 70 wt% of (i) + (ii), and the amounts of (i) and (ii) are based on the total weight of the polyethylene composition (B), the total weight being 100%, And the amounts of components (A) and (B) are based on the total weight of (A) + (B).
2. The polyolefin composition (I) according to claim 1, comprising 40 to 80 wt% of the heterophasic polymer composition (A) and 20 to 60 wt% of the polyethylene composition (B).
3. The polyolefin composition (I) according to claim 1 or 2, wherein the component (A) is a heterophasic polymer composition comprising: (a) 35 to 70 wt.% of at least one propylene polymer selected from the group consisting of propylene homopolymers, propylene and ethylene and / or at least one copolymer of the formula CH2=CHR 1 A copolymer of α-olefins, wherein R 1 is a linear or branched C2 to C8 alkyl group, the copolymer comprising up to and including 10.0 wt% of units derived from ethylene and / or the α-olefin, based on the weight of (a); (b) 15 to 40% by weight of at least one ethylene and at least one compound of the formula CH2=CHR 1 A copolymer of α-olefins, wherein R 1 is a linear or branched C2 to C8 alkyl group, the copolymer comprising from 10 to 40% by weight of units derived from the α-olefin based on the weight of (b); (c) 5 to 30% by weight of at least one propylene and ethylene and / or at least one compound of the formula CH2=CHR 1 Copolymers of α-olefins and mixtures thereof, wherein R 1 is a linear or branched C2 to C8 alkyl group, the propylene copolymer comprises up to and including 50 wt. % by weight of (c) of units derived from ethylene and / or the α-olefin, The amounts of components (a), (b) and (c) are based on the total weight of (a) + (b) + (c).
4. The polyolefin composition (I) according to claim 1 or 2, wherein the at least one α-olefin included in the heterophasic polymer composition (A) is selected from the group consisting of butene-1, hexene-1, 4-methyl-1-pentene, octene-1 and combinations thereof.
5. The polyolefin composition (I) according to claim 1 or 2, wherein the polyethylene composition (B) comprises: (i) 25 to 85 wt.% of a polyethylene component having a weight average molecular weight Mw(i) equal to or higher than 1,000,000 g / mol as measured by gel permeation chromatography; (ii) 10 to 65 wt% of a polyethylene component having a weight average molecular weight Mw(ii) equal to or lower than 5,000 g / mol as measured by gel permeation chromatography; (iii) up to and including 100% by weight of a polyethylene component other than component (i) and component (ii), The polyethylene composition (B) comprises at least 70 wt% of (i) + (ii), and the amounts of components (i) and (ii) are based on the total weight of the polyethylene composition (B), and the total weight is 100%.
6. The polyolefin composition (I) according to claim 1 or 2, wherein the polyethylene component included in the polyethylene composition (B) is an ethylene homopolymer.
7. The polyolefin composition (I) according to claim 1 or 2, wherein the polyethylene composition (B) has a Mw / Mn (B) value equal to or greater than 300, and the polyethylene components (i) and (ii) have Mw / Mn independently selected from values up to and including 5, wherein Mw is the weight average molecular weight and Mn is the number average molecular weight measured by GPC.
8. The polyolefin composition (I) according to claim 1 or 2, wherein the polyethylene composition (B) has a melt flow rate MFR (B) up to and including 10 g / 10 min measured according to ISO 1133-2:2011 at 190°C and a load of 2.16 Kg.
9. The polyolefin composition (I) according to claim 1 or 2, further comprising up to and including 40 wt.% of a component (C) selected from the group consisting of: (C1) enhancer; (C2) saturated or unsaturated styrene or α-methylstyrene block copolymers comprising up to and including 30% by weight of polystyrene, based on the weight of (C2); (C3) polyolefins functionalized with a compound selected from the group consisting of maleic anhydride, C1 to C10 linear or branched dialkyl maleates, C1 to C10 linear or branched dialkyl fumarates, itaconic anhydride, C1 to C10 linear or branched itaconic acid, dialkyl esters, maleic acid, fumaric acid, itaconic acid; (C4) additives selected from the group consisting of pigments, dyes, extender oils, flame retardants, anti-UV agents, UV stabilizers, lubricants, anti-blocking agents, slip agents, waxes; (C5) Their combination, The amount of component (C) is based on the total weight of (A) + (B) + (C).
10. The polyolefin composition (I) according to claim 1, wherein: The copolymer in (a) comprises from 0.05 to 8.0 wt. %, based on the weight of (a), of units derived from ethylene and / or the α-olefin; and / or The copolymer in (b) comprises from 20 to 35 wt% of units derived from the α-olefin, based on the weight of (b).
11. The polyolefin composition (I) according to claim 1, comprising 50 to 70 wt% of the heterophasic polymer composition (A) and / or 30 to 50 wt% of the polyethylene composition (B).
12. The polyolefin composition (I) according to claim 3, wherein the content of propylene polymer in (a) is from 40 to 65 wt. %; and / or the copolymer in (a) comprises from 0.05 to 8.0 wt. %, based on the weight of (a), of units derived from ethylene and / or α-olefins; and / or the content of the copolymer in (b) is from 20 to 35 wt. %; and / or the copolymer in (b) comprises from 20 to 35 wt. %, based on the weight of (b), of units derived from α-olefins; and / or the content of the copolymer in (c) is from 7 to 20 wt. %; and / or the copolymer in (c) comprises from 15 to 50 wt. %, based on the weight of (c), of units derived from ethylene and / or α-olefins.
13. The polyolefin composition (I) according to claim 1 or 2, wherein the at least one alpha-olefin comprised in the heterophasic polymer composition (A) is butene-1.
14. The polyolefin composition (I) according to claim 5, wherein the content of the polyethylene component in (i) is 60 to 75 wt%; and / or the content of the polyethylene component in (ii) is 10 to 20 wt%; and / or the content of (i) + (ii) is at least 75 wt%.
15. The polyolefin composition (I) according to claim 14, wherein the content of (i) + (ii) is at least 80% by weight.
16. The polyolefin composition (I) according to claim 7, wherein the polyethylene composition (B) has a Mw / Mn (B) value of 300 to 1,500; and / or the polyethylene components (i) and (ii) have Mw / Mn values independently selected from 1.2 to 5.
17. The polyolefin composition (I) according to claim 16, wherein the polyethylene components (i) and (ii) have Mw / Mn independently selected from values ranging from 1.5 to 4.
5.
18. The polyolefin composition (I) according to claim 1 or 2, wherein the polyethylene composition (B) has a melt flow rate MFR (B) of 0.00001 to 10 g / 10 min measured according to ISO 1133-2:2011 at 190°C and a load of 2.16 Kg.
19. The polyolefin composition (I) according to claim 9, wherein the content of component (C) is 0.5 to 30 wt%; and / or the saturated or unsaturated styrene or α-methylstyrene block copolymer comprises 10 to 30 wt% of polystyrene based on the weight of (C2).
20. The polyolefin composition (I) according to claim 19, wherein the content of component (C) is from 1 to 20 wt%.
21. A process for producing a shaped article, said process comprising subjecting a flow rate of a molten polyolefin composition (I) as defined in any one of claims 1 to 9 to a temperature equal to or greater than 50 s -1 The shear rate steps.
22. The process according to claim 21, wherein the flow rate of the molten polyolefin composition (I) as defined in any one of claims 1 to 9 is subjected to a temperature equal to or greater than 50 s. -1 The steps of shear rate are performed by injection molding or by extrusion based processes.
23. The process according to claim 21 or 22, wherein the flow rate of the molten polyolefin composition (I) as defined in any one of claims 1 to 9 is subjected to a temperature equal to or greater than 50 s. -1 The step of the shear rate is performed by injection molding, and the shear rate ranges from 50 to 3,000 s -1 .
24. The process according to claim 21 or 22, wherein the flow rate of the molten polyolefin composition (I) as defined in any one of claims 1 to 9 is subjected to a temperature equal to or greater than 50 s. -1 The shear rate step is performed by extrusion-based 3D printing, and the shear rate ranges from 50 to 1,000 s -1 , and optionally the strain rate ranges from 3 to 50 s -1 .
25. The process according to claim 21, wherein the process comprises subjecting the flow rate of the molten polyolefin composition (I) as defined in any one of claims 1 to 9 to a temperature equal to or greater than 150 s. -1 The shear rate steps.
26. The process according to claim 21 or 22, wherein the flow rate of the molten polyolefin composition (I) as defined in any one of claims 1 to 9 is subjected to a temperature equal to or greater than 50 s. -1 The step of the shear rate is performed by injection molding, and the shear rate ranges from 200 to 2,000 s -1 .
27. The process according to claim 21 or 22, wherein the flow rate of the molten polyolefin composition (I) as defined in any one of claims 1 to 9 is subjected to a temperature equal to or greater than 50 s. -1 The step of shear rate is performed by extrusion-based 3D printing, and the shear rate ranges from 100 to 600 s -1 , and optionally the strain rate ranges from 3 to 20 s -1 .
28. An article obtainable by a process as defined in any one of claims 21 to 27.
29. A filament for extrusion-based additive manufacturing comprising a polyolefin composition (I) as described in any one of claims 1 to 9.
30. Use of a polyethylene composition (B) as a reinforcement masterbatch of a heterophasic polymer composition (A), said polyethylene composition (B) comprising: (i) 25 to 85 wt.% of a polyethylene component having a weight average molecular weight Mw(i) equal to or higher than 1,000,000 g / mol as measured by gel permeation chromatography; (ii) 10 to 65% by weight of a polyethylene component having a weight average molecular weight Mw(ii) equal to or lower than 5,000 g / mol as measured by gel permeation chromatography, wherein the polyethylene composition (B) comprises at least 70 wt% of (i) + (ii), and the amounts of (i) and (ii) are based on the total weight of the polyethylene composition (B), the total weight being 100%, And the heterophasic polymer composition (A) comprises: (a) 50 to 80 wt% of at least one propylene polymer selected from the group consisting of a propylene homopolymer, a propylene and ethylene polymer and / or at least one copolymer of the formula CH2=CHR 1 Copolymers of α-olefins and mixtures thereof, wherein R 1 is a linear or branched C2 to C8 alkyl group, the copolymer comprising up to and including 10.0 wt% of units derived from ethylene and / or the α-olefin, based on the weight of (a); (b) 20 to 50% by weight of ethylene and at least one compound of the formula CH2=CHR 1 At least one copolymer of an α-olefin, wherein R 1 is a linear or branched C2 to C8 alkyl group, the copolymer comprises from 10 to 40% by weight of units derived from the α-olefin, based on the weight of (b), The amounts of components (a) and (b) are based on the total weight of (a) + (b).
31. The use according to claim 30, wherein: The copolymer in (a) comprises from 0.05 to 8.0 wt. %, based on the weight of (a), of units derived from ethylene and / or α-olefins; and / or the copolymer in (b) comprises from 20 to 35 wt. %, based on the weight of (b), of units derived from α-olefins.
Citation Information
Patent Citations
Components and catalysts for the polymerization of olefins
EP0045977A2
Diethers usable in the preparation of Ziegler-Natta catalysts and their preparation
EP0361493A1
Components and catalysts for the polymerization of olefins
EP0395083A2
Concentrates suitable for the preparation of functionalized polyolefins and functionalization process using said concentrates
EP0572028A1
Components and catalysts for the polymerization of olefins
EP0728769A1